CHARACTERIZATION AND POTENCY OF STICHOPUS HERMANNI ETHANOL EXTRACT ON ORAL WOUND HEALING - Rima Parwati Sari; Stevanus Candra Sugiarto Budijono (ODONTO : Dental Journal, 2020)
Background: Stichopus hermanni contains protein, glycosaminoglycans and EPA-DHA, which accelerate oral wound healing. Ethanol is solvent with universal nature and frequently used in the extraction. This study aims to know the characterization and potency of Stichopus hermanni in oral wound healing. Methods: Stichopus hermanni was dried by freeze-dry method and extracted using ethanol solvent. Characterization was examined the levels of protein, glycosaminoglycans and EPA-DHA. In vivo, male wistar rats made traumatic ulcer at the lower labial mucosa by using thermal burn. Thirty-two rats are divided into four groups (n=8), negative control group (K), positive control group (AH) was given hyaluronic acid gel 0.2%, and treatment groups were given Stichopus hermanni 60%-80% (SH60-SH80) gel. The ulcer formed was given gel for four days. The rat’s labial mucosa was measured. The difference between the first and fourth day is tabulated. Data were analyzed by Anova and Tukey-HSD tests. Results: The result of Spectrophotometry show the contents of protein (19.39), glycosaminoglycans (2.79–3.98). The result of in vivo showed a significant difference in ANOVA test (K=1.07; AH=1.27; SH60=1.89; SH80=1.66). In the Tukey-HSD test, the SH60 group shows a significant difference between K and AH groups. Conclusion: Stichopus hermanni ethanol extract gel contain protein and Glycosaminoglycans and potency for oral wound healing.